Prevalence of ECG abnormalities in chronic spinal cord injury patients with deranged lipid profile - Ashta, Kuldeep Kumar; Kumar, Ravi (International Journal of Advances in Medicine, 2017)
Background: Spinal cord injury (SCI) is a catastrophic, unfortunate event which results in profound disability and secondary complications like neurogenic shock, arrhythmias, autonomic dysfunction, pressure ulcers, etc. These patients are at increased risk for the cardiovascular risk factors (like obesity, dyslipidemia and diabetes) and cardiovascular complications due to hampered mobility and impaired autonomic system. Therefore, these patients with must be screened quite frequently for cardiovascular problems. Methods: The study was an analytic cross-sectional study, to assess the prevalence of ECG abnormalities and deranged lipid profiles in the spinal cord injury patients and to access the correlation between these two in chronic Spinal Cord Injury patients. The early morning fasting blood samples were collected for the lipid profile test and thrice daily resting 12 lead ECG were done for all the patients for a month and were analyzed in context with their previous available ECGs from their respective records. Results: A total of 52 SCI patients were taken up for the study, of them 30 was paraplegic and 22 were tertraplegic. Out of 52, lipid profiles were deranged in 31 patients of which 17 had normal ECG and lipid profile was normal in 21, of which only 1 patient had an ECG abnormality. It was found that that out of 52 patients cholesterol levels were deranged in 17 patients, LDL in 6, triglycerides in 15 patients and the values of HDL were normal in all. Conclusions: The most common abnormality found in this population of SCI patients was sinus bradycardia. There was only one ECG which showed T-wave abnormalities suggesting possible myocardial ischemia.